PACKAGING DESIGN AS COMMUNICATION WITH CUSTOMERS - Shoponiak, Yuliia (European Journal of Interdisciplinary Issues, 2025)
The article is devoted to the analysis of the influence of packaging design on consumer choice and brand communication with the client. The purpose of the study is to find out how packaging design affects consumer choice and brand communication with the client. In the course of the scientific study, general scientific methods of cognition were used: analysis, synthesis, induction, deduction, observation and generalization. The results of the study show that packaging is a key element of visual communication, as it forms the first impression of the product even before its use. Visual characteristics – shape, color, typography, composition – act as markers of the quality, value and positioning of the product. Tactile properties of packaging, such as surface texture, create a sensory experience that enhances emotional engagement and consolidates associations with the brand. It has been proven that color has an extremely strong influence on perception: it forms recognition, causes associations with the product category and stimulates the consumer’s emotional reaction. Packaging performs the functions of multi-level communication: it informs, differentiates, emotionally engages and forms loyalty. The use of elements such as a logo, a unified color palette and identity creates a holistic visual system that ensures brand consistency at all points of contact. Of particular importance is the integration of digital solutions – QR codes, AR technologies, digital-first strategies, which transform packaging into a tool for two-way interaction between the brand and the consumer in a virtual environment. It is shown that packaging not only presents the product, but also represents the brand, its values, promises, positioning and lifestyle with which the consumer wants to identify. In general, it is proven that effective packaging design is the result of a harmonious combination of visual identity, emotional impact and strategic communication. The practical significance of the study is that its results can be used to create packaging that not only protects the product, but also effectively communicates with the target audience, increases sales, and strengthens brand identity.